DNA damage stress-induced translocation of mutant FUS proteins into cytosolic granules and screening for translocation inhibitors - Nogami, Masahiro; Sano, Osamu; Adachi-Tominari, Keiko; Hayakawa-Yano, Yoshika; Furukawa, Takako; Iwata, Hidehisa; Ogi, Kazuhiro; Okano, Hideyuki; Yano, Masato (Frontiers in Molecular Neuroscience, 2022)
Fused in sarcoma/translated in liposarcoma (FUS) is an RNA-binding protein, and its mutations are associated with neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS), through the DNA damage stress response, aberrant stress granule (SG) formation, etc. We previously reported that translocation of endogenous FUS into SGs was achieved by cotreatment with a DNA double-strand break inducer and an inhibitor of DNA-PK activity. In the present study, we investigated cytoplasmic SG formation using various fluorescent protein-tagged mutant FUS proteins in a human astrocytoma cell (U251) model. While the synergistic enhancement of the migration of fluorescent protein-tagged wild-type FUS to cytoplasmic SGs upon DNA damage induction was observed when DNA-PK activity was suppressed, the fluorescent protein-tagged FUSP525L mutant showed cytoplasmic localization. It migrated to cytoplasmic SGs upon DNA damage induction alone, and DNA-PK inhibition did not show a synergistic effect. Furthermore, analysis of 12 sites of DNA-PK–regulated phosphorylation in the N-terminal LC region of FUS revealed that hyperphosphorylation of FUS mitigated the mislocalization of FUS into cytoplasmic SGs. By using this cell model, we performed screening of a compound library to identify compounds that inhibit the migration of FUS to cytoplasmic SGs but do not affect the localization of the SG marker molecule G3BP1 to cytoplasmic SGs. Finally, we successfully identified 23 compounds that inhibit FUS-containing SG formation without changing normal SG formation.